Body Mass Index (BMI) and Waist Circumference Levels of Belly Dance Participants at Purnama Studio - Nur Latifah; Perdinanto; Akhmad Amirudin (Universitas Negeri Semarang, 2025)
This study aims to determine the Body Mass Index (BMI) levels and waist circumference of Belly Dance participants at Sanggar Purnama. This research employed a descriptive quantitative method using a total sampling technique, involving 15 active Belly Dance participants. The instruments used included BMI measurements and waist circumference. The results showed that most participants (40%) fell into the obesity category I, 26.67% were overweight, 26.67% were in the normal range, and 6.67% were classified as obesity category II. Regarding waist circumference, 53% of participants were within the normal range, while 47% exceeded the normal threshold for women (>80 cm), indicating central obesity. These findings suggest that although Belly Dance is regularly practiced, not all participants achieved ideal body weight or waist circumference. This highlights the importance of a holistic approach to weight management, incorporating regular physical activity, a balanced diet, and a healthy lifestyle. This study contributes to the understanding of Belly Dance’s effectiveness on body composition and participant health and serves as a foundation for future health intervention strategies.